Theoretical notes on the role of the reader in integrated microfiction - Galindo Rojas, Percy (2021)
This paper analyzes the role of the reader in integrated microfiction (IM), a border textual modality that incorporates two discursive forms of relative recent critical interest: microfiction, a hyperonym that include short and very brief texts of various forms, and integrated texts, series or collections of short texts that, due to common links of form and / or substance, offer the possibility of being read together or independently.